Acute Side Effects of Radiation Therapy : A Guide to Management - Sourati, Ainaz; Ameri, Ahmad; Malekzadeh, Mona (Springer International Publishing : Imprint: Springer, 2017)
This book provides clear guidance on how to manage a wide range of side effects frequently encountered when treating patients with radiation therapy. For each potential side effect, incidence, mechanism, symptoms, and grading are carefully described. All aspects of management are addressed, drawing on the latest available evidence and highlighting key details of importance in clinical routine. The introduction of new radiation therapy techniques such as 3D conformal radiation therapy, intensity-modulated radiation therapy, and image-guided radiation therapy has reduced normal tissue doses and, accordingly, treatment complications. Nevertheless, a significant percentage of patients still experience acute side effects, in part because the threshold doses for these toxicities are typically lower than those for late effects. Acute toxicities may lead to interruption of treatment and be associated with an increase in late damage. A swift and effective response is therefore essential. This book will enable the reader to provide effective care for each side effect, thereby improving patient compliance with treatment and treatment outcomes.
Keywords: Medicine.; Radiotherapy.; Oncology.; elektronické knihy; electronic books